2022
DOI: 10.3390/toxins15010013
|View full text |Cite
|
Sign up to set email alerts
|

Spirolides in Bivalve Mollusk of the Galician (NW Spain) Coast: Interspecific, Spatial, Temporal Variation and Presence of an Isomer of 13-Desmethyl Spirolide C

Abstract: Spirolides are cyclic imines whose risks to human health have not been sufficiently evaluated. To determine the possible impact of these compounds in Galicia (NW Spain), their presence and concentration in bivalve mollusk were studied from 2014 to 2021. Only 13-desmethyl spirolide C (13desmSPXC) and an isomer have been detected, and always at low concentrations. Mussel, Mytilus galloprovincialis, was the species which accumulated more spirolides, but the presence of its isomer was nearly restricted to cockle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…SPX-1 and GYM-A have a greater presence during the autumn/winter period and then decrease, appearing in trace concentration values during the spring/summer period (Figures 3 and 6). The same seasonal pattern of SPX-1 was observed in Blanco et al [21], where the highest levels were found during the late autumn-early winter and the lowest at the end of summer [21]. In accordance with Lamas et al [34], the maximum percentage of GYM-A prevalence was in February and the minimum was in July in Galician waters (Spain) [29].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…SPX-1 and GYM-A have a greater presence during the autumn/winter period and then decrease, appearing in trace concentration values during the spring/summer period (Figures 3 and 6). The same seasonal pattern of SPX-1 was observed in Blanco et al [21], where the highest levels were found during the late autumn-early winter and the lowest at the end of summer [21]. In accordance with Lamas et al [34], the maximum percentage of GYM-A prevalence was in February and the minimum was in July in Galician waters (Spain) [29].…”
Section: Discussionsupporting
confidence: 80%
“…Spirolides, including SPX-1, in mussels ( M. galloprovincialis ) from Galicia (NW Spain) were recorded, presenting low levels ranging from 1.2 µg/kg to 6.9 µg/kg of SPX-1 [ 35 ] in 18 samples sampled in May 2015. This study has just been updated with an eight-year study by Blanco et al [ 21 ], describing the 75% of the results below 10 µg/kg with a maximum of 80 µg/kg for SPX-1 from 2014 to 2021 [ 21 ]. SPX-1 was also described in Lake Ingril, France (from 1 µg/kg to 19 µg/kg of SPX-1) [ 29 ], in the four-year survey on that area and in the EMERGTOX project from 2018 to 2022, where spirolides (SPX-1 and SPX-DesMeD) were systematically present with a maximum concentration of 69 µg/kg [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Europe, SPX was found in shellfish in Norway [ 9 ], Spain [ 63 , 64 ], and Italy [ 65 ], whereas PnTX was found in mussels in various parts of the Norwegian coast [ 13 , 66 ]. Recently, a three-year survey (2019–2021) was carried out in Greece on the contamination of shellfish by cyclic imines, implementing an LC-MS/MS method.…”
Section: Discussionmentioning
confidence: 99%